Impure migration : Jews and sex work in golden age Argentina - Yarfitz, Mir (Jewish cultures of the world., 2019)
Impure Migration investigates the period from the 1890s until the 1930s, when prostitution was a legal institution in Argentina and the international community knew its capital city Buenos Aires as the center of the sex industry. At the same time, pogroms and anti-Semitic discrimination left thousands of Eastern European Jewish people displaced, without the resources required to immigrate. For many Jewish women, participation in prostitution was one of very few ways they could escape the limited options in their home countries, and Jewish men facilitate their transit and the organization of their work and social lives. Instead of marginalizing this story or reading it as a degrading chapter in Latin American Jewish history, Impure Migration interrogates a complicated social landscape to reveal that sex work is in fact a critical part of the histories of migration, labor, race, and sexuality.